Mechanical, fracture, and environmental performance of greener polymer composites containing low to high micro fillers with recycled and byproduct origins - Khedri, Ehsan; Karimi, Hamid Reza; Mohamadi, Razie; Aliha, M. R. M.; Nejad, Reza Masoudi (Wiley, 2024)
Polymer adhesives have considerable mechanical and environmental privileges; however, their high price makes them uncommercial for common uses. This study investigates the incorporation of recycled or byproduct fillers in epoxy resin-based composites to assess their mechanical properties, environmental impacts, and cost efficiency. The fillers examined include fly ash, glass powder, slag, silica powder, and limestone powder. Tensile, compressive, and fracture tests were conducted on composites with various filler proportions (0%-80% by weight). From microstructure observations, round (fly ash, glass powder) and rough (slag, silica, and limestone powder) morphologies are seen. Also, it is seen that all the fillers are well distributed in the matrix; with the increase of filler content, the air voids increase. The tensile and compressive results indicate that adding fillers improves the composite's strengths, with up to a 20% increase compared to neat epoxy resin. However, when filler contents exceed 40%, the strengths decrease. Fracture toughness values also decrease with increasing filler content. Comparing the results with those of other studies indicates the similarity of trends. Cost-strength and CO2eq-strength curves were evaluated to assess the financial and environmental aspects. The composites show potential for cost efficiency but may have some environmental drawbacks compared to traditional construction materials like cement concrete.
Keywords: byproduct and recycled; cost analysis; environmental impact; epoxy resin; filler; mechanical behavior